Hubungan Antara Gaya Hidup Dengan Keputusan Pembelian Online Shopee Di Masa Pandemi Covid-19 Pada Mahasiswi Jurusan Manajemen Universitas Muhammadiyah Palembang - Prameswari Indriyani; listya Istiningtyas (Indonesian Journal of Behavioral Studies, 2021)
This study aims to determine the relationship between lifestyle and Shopee online purchasing decisions during the Covid-19 Pandemic in Management Students, University of Muhammadiyah. Lifestyle is related to how a person spends his time, what is important for people to consider in the environment, and what people think about themselves and the world around them, while purchasing decisions are decisions that are initiated by consumers to buy goods or services in exchange for money in the process. buying and selling goods or services. The population in this study amounted to 287 female students while the subjects of this study amounted to 158 students of the Management Department of Muhammadiyah University of Palembang, Class of 2018. Data collection used a lifestyle scale and a purchasing decision scale. This study uses correlational quantitative methods with Pearson's product moment analysis. The results of the study revealed that there was a significant positive relationship between lifestyle and Shopee online purchasing decisions during the Covid-19 Pandemic for Management Students at Muhammadiyah University of Palembang, this was evidenced by the correlation coefficient r= 0.535 (p < 0.01), meaning that The higher the lifestyle, the higher the purchase decision, on the contrary, the higher the purchase decision, the higher the lifestyle in female students.